A Comprehensive Bibliometric Analysis of Real Estate Research Trends - Salma El Bied; Lorenzo Ros Mcdonnell; Ma Victoria de-la-Fuente-Aragón; Diego Ros Mcdonnell (International Journal of Financial Studies)
Real estate, characterized by its diverse and complex nature, presents a multifaceted research domain. It encompasses various topics and challenges, making it both content-wise challenging and multidimensional. This study aims to conduct a knowledge mapping of the literature in the real estate field using a sample of 9700 document articles published between 1929 and 2023 based on publications indexed in the Web of Science database. This study utilizes the software SciMAT (version 1.1.04) to demonstrate hot keywords and trends in this field and additionally employs the VOSviewer (version 1.6.19) tool to analyze keywords, countries, authors, and sources. Authors reveal a growing interest in real estate literature, with the USA contributing the most publications, while relatively few originate from Africa and South America. This study investigates the strategic themes and the scientific evolution structure, provides a comprehensive examination of the current state of real estate literature, and helps in understanding its development. It offers a valuable reference point for future research in this domain.